Retrieving the tradition: Salvino Busuttil, “Morality and Economic Development”: excerpts from Melita Theologica 17/1 (1965) : 19-24 - Busuttil, Salvino (Melita theologica, 2019)
When, nearly ten years ago, I first started studying philosophy, I remember asking one of my tutors over lunch what philosophy was actually all about. “Imagine,” he said referring to the table in front of him, “that this table had no legs.” “I am imagining,” I said. “Good. Imagine now that it had no surface and no sides.” I looked hungrily at the dishes on the table - at which point, my professor, rather uncharitably said, “Imagine now that there was nothing on the surface. What remains?” “Nothing,” I replied, eyeing the dishes even more hungrily. “Good,” he said. “Now you know what philosophy is all about.”